Formation of A Group of Women of Fertilizing Age (Wus) Caring for Stunting and Prevention of Early Marriage - Elly Wahyuni; Mariati Mariati; Lusi Andriani; Rina Rina (Asosiasi Profesi Multimedia Indonesia, 2023)
43.5% of stunting cases in Indonesia occur in children under 3 years of age whose mothers are aged between 14-15 years, while 22.4% occur with mothers aged between 16-17 years. The proportion of women of childbearing age (WUS) who were at risk of experiencing CED in Indonesia in 2017 was 10.7%, while the proportion of pregnant women who were at risk of experiencing CED was 14.8%. Based on an analysis of the situation in Tumbuan Village, Lubuk Sandi District, data was obtained that the population = 2021 people, the number of families = 573 families, the number of couples of childbearing age (PUS) = 306 couples while the number of teenagers 12-19 years = 285 people. With the high number of stunting sufferers in Tumbuan Village, and the large number of Women of Childbearing Age, we intend to carry out activities to form a group of women of childbearing age (WUS) to care about stunting and prevent early marriage in Tumbuan Village. In this research, pre-test and post-test methods were used. This service activity was carried out by forming a Group of Women of Childbearing Age (WUS) Caring for Editing and Preventing Early Marriage. The results of this community service showed an increase in the knowledge of the WUS group in Tumbuan Village, Lubuk Sandi District with an average increase of 4.8.